Styrenic resin foam molded product, method for producing expandable styrene resin particles, and method for producing styrene resin foam molded product
By controlling the surface characteristics of styrene-based resin foam molded products, specifically the average number of holes, surface roughness, and bubble diameter, using foamable styrene resin particles with additives, the product achieves excellent gloss and smoothness.
Patent Information
- Application Number
- JP2020210463
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-29
- Filing Date
- 2020-12-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Existing styrene-based resin foam molded products struggle to achieve a beautiful and glossy appearance due to surface roughness and irregularities.
The styrene-based resin foam molded article is produced by controlling the average number of holes per unit area on the surface of the styrene-based resin particles, surface roughness, and average bubble diameter, using foamable styrene resin particles with specific additives such as polyethylene glycol and aliphatic compounds.
This approach results in a styrene-based resin foam molded product with excellent gloss, surface smoothness, and enhanced product value.
Smart Images

Figure 0007671579000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a styrene-based resin foamed molded article, a method for producing expandable styrene-based resin particles, and a method for producing a styrene-based resin foamed molded article. [Background technology]
[0002] Since foam molded articles are lightweight and have excellent heat insulating properties and mechanical strength, they are widely used as heat insulating materials for houses and automobiles, heat retaining materials for building materials, transport packaging materials for fish boxes and food containers, cushioning materials, etc. Among them, in-mold foam molded articles produced from expandable particles as a raw material are widely used because of advantages such as the ease of obtaining a desired shape. Foam molded articles are desired to have a beautiful and glossy appearance, but various issues remain to be investigated in order to realize such an appearance. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-070150 A [Patent Document 2] Patent No. 5014653 [Patent Document 3] Patent No. 4925620 [Patent Document 4] Patent No. 4982302 Summary of the Invention [Problem to be solved by the invention]
[0004] The main object of the present invention is to provide a styrene-based resin foamed molded article having excellent gloss. The present invention also provides a method for producing expandable styrene-based resin particles capable of realizing such a foamed molded article, and a simple and inexpensive method for producing such a foamed molded article. [Means for solving the problem]
[0005] The styrene-based resin foamed molded product according to the embodiment of the present invention contains expanded styrene-based resin particles obtained by expanding pre-expanded styrene-based resin particles, and is composed of a plurality of the expanded styrene-based resin particles fused to each other. The average number of pores on the surface of the expanded styrene-based resin particles present on the surface of the styrene-based resin foamed molded product is 20 pores / mm 2 is less than. In one embodiment, the surface roughness Rzjis94 of the expanded styrene resin particles present on the surface of the styrene resin expansion molded article is 1 μm to 25 μm. In one embodiment, the surface layer of the styrene-based resin foam molded article has an average cell diameter of 25 μm to 250 μm. In one embodiment, the residual monomer content of the expandable styrene-based resin particles forming the pre-expanded styrene-based resin particles is 200 ppm to 10,000 ppm, and the content of the surface additive in the expandable styrene-based resin particles is 0.05% by weight to 0.5% by weight. In one embodiment, the surface additive contains polyethylene glycol, and the content of the polyethylene glycol in the expandable styrene-based resin particles is 0.01% by weight to 0.1% by weight. In one embodiment, the surface additive contains an aliphatic compound that is liquid at 5° C., and the content of the aliphatic compound in the expandable styrene-based resin particles is 0.01% by weight to 0.3% by weight. In one embodiment, the lipid compound that is liquid at 5° C. is a medium-chain fatty acid triglyceride. In one embodiment, the surface additive includes a metal salt of a higher fatty acid, and the content of the metal salt of a higher fatty acid in the expandable styrene-based resin particles is 0.0025% by weight to 0.475% by weight. In one embodiment, the metal salt of a higher fatty acid is at least one selected from zinc stearate and magnesium stearate. According to yet another aspect of the present invention, there is provided a method for producing expandable styrene-based resin particles, which comprises the steps of polymerizing a styrene-based monomer, impregnating the expandable particles with a blowing agent simultaneously with or after the polymerization to obtain expandable particles, and applying a surface additive containing polyethylene glycol and / or an aliphatic compound that is liquid at 5°C to the expandable particles. According to yet another aspect of the present invention, there is provided a method for producing the above-mentioned styrene-based resin foamed molded article, which uses the expandable styrene-based resin particles obtained by the above-mentioned production method. Effect of the Invention
[0006] According to an embodiment of the present invention, in a styrene-based resin foamed molded product, by controlling the average number of holes per unit area on the surface of the expanded styrene-based resin particles present on the surface of the foamed molded product within a predetermined range, it is possible to realize a styrene-based resin foamed molded product having excellent gloss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments. The definitions of terms used in this specification are as follows. Styrene-based resin foamed molded product (sometimes simply referred to as foamed molded product): refers to a molded product that is foamed into a specified shape and is composed of foamed styrene-based resin particles obtained by expanding pre-expanded styrene-based resin particles. Expandable styrene-based resin particles (sometimes simply referred to as expandable particles): These refer to particles impregnated with a blowing agent before foaming. Pre-expanded styrene-based resin particles (sometimes simply referred to as pre-expanded particles): These refer to particles obtained by expanding expandable particles, and which can be further expanded to form a foamed molded article. Expanded styrene-based resin particles (sometimes simply referred to as expanded particles): These refer to particles obtained by further expanding pre-expanded styrene-based resin particles that constitute the foamed molded article.
[0008] In this specification, "weight" and "mass" have the same meaning. Therefore, for example, "wt%" may be read as "mass%", and "parts by weight" may be read as "parts by mass".
[0009] A. Styrene resin foam molding The styrene-based resin foamed molded article according to the embodiment of the present invention contains expanded styrene-based resin particles obtained by expanding pre-expanded styrene-based resin particles. More specifically, the foamed molded article is constituted by a plurality of expanded particles fused together by foaming the pre-expanded particles in a mold of a predetermined shape, and has a shape corresponding to the mold. In the embodiment of the present invention, the average number of pores on the surface of the expanded particles present on the surface of the foamed molded article is 20 pores / mm 2 With such a configuration, a foamed molded article having excellent gloss can be realized. The average number of pores on the surface of the foamed particles present on the surface of the foamed molded article is preferably 15 pores / mm 2 More preferably, 8 particles / mm 2 More preferably, 5 / mm 2 3.5 pieces / mm or less, and particularly preferably 3.5 pieces / mm 2 0.01 to 0.05, and more preferably 0.01 to 0.05. 2 The smaller the average number of holes, the more preferable it is, and the lower limit is, for example, 0.03 holes / mm 2 The surface pores, in other words, mean breaks in the surface of the foamed beads. The average number of pores per unit area on the surface of the foamed beads can be obtained from a scanning electron microscope (SEM) image of an arbitrarily selected predetermined region of the foamed molded article. According to an embodiment of the present invention, by controlling the average number of pores per unit area on the surface of the foamed beads present on the surface of the foamed molded article to the above-mentioned predetermined range, a foamed molded article having excellent gloss can be realized. The foamed molded article according to the embodiment of the present invention is beautiful and has very high commercial value.
[0010] The surface roughness Rzjis94 of the expanded particles present on the surface of the foamed molded article is preferably 1 μm to 25 μm, more preferably 1 μm to 18 μm, even more preferably 1 μm to 14 μm, and particularly preferably 1 μm to 10 μm. The surface roughness Rzjis94 may be, for example, 5 μm to 9 μm. If the surface roughness Rzjis94 is in such a range, a foamed molded article having a better gloss can be realized due to the synergistic effect of optimizing the average cell diameter of the surface layer of the pre-expanded particles and the average number of holes per unit area of the surface of the expanded particles. The surface roughness Rzjis94 means the ten-point average roughness. The surface roughness Rzjis94 can be measured, for example, using a surface roughness shape measuring instrument so as not to measure the seams between the expanded particles.
[0011] The average bubble diameter of the surface layer of the foamed molded product is preferably 25 μm to 250 μm, more preferably 35 μm to 190 μm, further preferably 45 μm to 140 μm, and particularly preferably 50 μm to 130 μm. With such a configuration, a foamed molded product having excellent gloss can be obtained. If the average bubble diameter is too large, the surface unevenness may become large, resulting in insufficient gloss and insufficient mechanical strength. If the average bubble diameter is too small, the surface of the foamed molded product may be torn (a state in which the foamed particles melt and sink or shrink) during molding, resulting in insufficient appearance beauty. The surface layer of the foamed molded product refers to a region from the surface of the foamed molded product to 500 μm inward in a direction perpendicular to the surface. The average bubble diameter can be measured in accordance with ASTM D2482-69. An example of a specific method for measuring the average bubble diameter is described in the examples described later.
[0012] The average bubble diameter of the surface layer of the pre-expanded particles that can form the foamed molded product is, for example, 20 μm to 200 μm, preferably 25 μm to 180 μm, more preferably 40 μm to 120 μm, and further preferably 42 μm to 100 μm. The surface layer of the pre-expanded particles refers to a region from the surface of the pre-expanded particles to 200 μm in the center direction (i.e., in the diameter direction). The average bubble diameter can be measured in accordance with ASTM D2482-69, as in the case of the above-mentioned molded product. An example of a specific method for measuring the average bubble diameter is described in the examples below.
[0013] The expandable particles and pre-expanded particles capable of forming a foamed molded article will be described below, followed by a description of the methods for producing the expandable particles and the foamed molded article.
[0014] B. Expandable styrene resin particles The expandable particles typically contain a styrene resin, a foaming agent, and a surface additive, and have a particle shape as a whole. The particle size of the expandable particles is, for example, 0.3 mm to 3.0 mm, and preferably 0.3 mm to 1.7 mm. The particle size can be measured in accordance with JIS Z 8815. Specifically, the particle size is the value measured as a particle size at an integrated value of 50% from the particle size distribution by the sieving test of JIS Z 8815. Any appropriate shape can be adopted as the shape of the expandable particles. Specific examples of the shape include a spherical shape, a nearly spherical shape, an oval spherical shape (egg-shaped), a cylindrical shape, and a nearly cylindrical shape.
[0015] The expandable particles preferably have a residual monomer content of 10000 ppm or less, more preferably 8000 ppm or less, further preferably 6000 ppm or less, and particularly preferably 5500 ppm or less. The residual monomer content may be, for example, 200 ppm to 500 ppm. If the residual monomer content of the expandable particles is within such a range, it may be easy to control the average cell diameter of the surface layer part of the pre-expanded particles and the average number of holes per unit area of the surface of the expanded particles within the above-mentioned predetermined range. Furthermore, since the flexibility of the resin can be ensured, a foamed molded article having a smooth surface can be obtained. As a result, a foamed molded article having excellent gloss can be realized.
[0016] The content of the surface additive in the expandable particles is preferably 0.05% by weight to 0.5% by weight, more preferably 0.05% by weight to 0.4% by weight, further preferably 0.1% by weight to 0.35% by weight, and particularly preferably 0.15% by weight to 0.35% by weight. When the content of the surface additive is in such a range, it may be easy to control the average bubble diameter of the surface layer part of the pre-expanded particles and the average number of holes per unit area of the surface of the expanded particles to the above-mentioned predetermined range. As a result, it is possible to realize a foamed molded product having excellent gloss. The content of the surface additive in the expandable particles is substantially the amount of the surface additive attached to the surface of the expandable particles, and may correspond to the amount of the surface additive applied during production. The content of the surface additive in the expandable particles may be measured, for example, as the amount of the surface additive extracted with a predetermined solvent (e.g., methanol). The specific configuration of the surface additive will be described later.
[0017] B-1. Styrene-based resin The styrene resin is a polymeric compound containing a styrene monomer as a monomer component. The styrene monomer contains styrene or a styrene derivative. Examples of the styrene derivative include α-methylstyrene, vinyltoluene, chlorostyrene, ethylstyrene, i-propylstyrene, dimethylstyrene, and bromostyrene. The styrene monomer may be used alone or in combination of two or more. The styrene monomer preferably contains at least styrene. The styrene monomer preferably contains 50% or more of styrene based on the total amount of the styrene monomer, more preferably 70% or more, and even more preferably 90% or more.
[0018] The styrene resin may contain a styrene monomer as the main component of the monomer components, and may be a copolymer of a styrene monomer and a copolymer component. A representative example of the copolymer component is a vinyl monomer. In this specification, the term "main component" means that the copolymer contains preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more of the styrene monomer.
[0019] Examples of the vinyl monomer include polyfunctional monomers, (meth)acrylic acid ester monomers, maleic acid ester monomers, and fumaric acid ester monomers. The vinyl monomers may be used alone or in combination of two or more kinds.
[0020] Specific examples of the polyfunctional monomer include divinylbenzenes such as o-divinylbenzene, m-divinylbenzene, and p-divinylbenzene, and alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate and polyethylene glycol di(meth)acrylate. By using the polyfunctional monomer, a branched structure can be imparted to the styrene-based resin. The content of the polyfunctional monomer in the styrene-based resin is preferably 0% by mass to 0.1% by mass, and more preferably 0.005% by mass to 0.05% by mass.
[0021] Specific examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and hexyl (meth)acrylate. Butyl acrylate, 2-ethylhexyl acrylate, and ethyl acrylate are preferred, and butyl acrylate is more preferred. By using the (meth)acrylic acid ester monomer, the glass transition temperature (Tg) of the styrene-based resin can be lowered. The content of the acrylic acid ester monomer in the styrene-based resin is preferably 0% by mass to 4.0% by mass, and more preferably 0.1% by mass to 3.0% by mass. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.
[0022] An example of a maleate monomer is dimethyl maleate.
[0023] Examples of fumarate monomers include dimethyl fumarate, diethyl fumarate, and ethyl fumarate.
[0024] B-2. Foaming agent Any suitable foaming agent can be used as the foaming agent. The foaming agent is preferably an organic compound whose boiling point is equal to or lower than the softening point of the styrene-based resin and is in a gaseous or liquid state at normal pressure. Specific examples include aliphatic hydrocarbons such as propane, n-butane, isobutane, pentane (n-pentane, isopentane or neopentane), and n-hexane; alicyclic hydrocarbons such as cyclopentane and cyclopentadiene; ketones such as acetone and methyl ethyl ketone; alcohols such as methanol, ethanol, and isopropyl alcohol; low-boiling ether compounds such as dimethyl ether, diethyl ether, dipropyl ether, and methyl ethyl ether; and halogen-containing hydrocarbons such as trichloromonofluoromethane and dichlorodifluoromethane. Inorganic gases such as carbon dioxide, nitrogen, and ammonia may be used as the foaming agent. The foaming agent may be used alone or in combination of two or more. Aliphatic hydrocarbons are preferred. This is because they can prevent the destruction of the ozone layer and can be quickly replaced with air, thereby suppressing the deterioration of the foamed molded product over time. More preferred are propane, n-butane, isobutane, n-pentane, isopentane, and combinations thereof.
[0025] The content of the foaming agent in the expandable particles can be appropriately set depending on the purpose as long as it is an amount sufficient to form pre-expanded particles and foamed molded articles. The content of the foaming agent is preferably 2 to 16 parts by mass, more preferably 3 to 8 parts by mass, based on 100 parts by mass of the styrene-based resin.
[0026] B-3. Surface additives The surface additive is typically applied to the surface of the expandable particle, and can appropriately modify the surface properties of the expandable particle depending on the purpose. Examples of the surface additive include a binding inhibitor, a fusion promoter, a spreading agent, and an antistatic agent. By appropriately setting the type, number, combination, content, etc. of the additive, the average bubble diameter of the surface layer of the pre-expanded particle and the average number of holes per unit area of the surface of the expanded particle can be controlled within the above-mentioned predetermined range. The content of the surface additive in the expandable particle is as described above.
[0027] The surface additive preferably contains polyethylene glycol. Polyethylene glycol can function, typically, as a spreading agent and an antistatic agent. By introducing polyethylene glycol into the surface additive, the average bubble diameter of the surface layer of the pre-expanded particles and the average number of holes per unit area on the surface of the expanded particles can be controlled within the above-mentioned predetermined range. In particular, the average number of holes per unit area on the surface of the expanded particles can be reduced. This is presumably because, since most surface additives are powders while polyethylene glycol is liquid, by introducing polyethylene glycol into the surface additive, the surface additive is uniformly spread on the surface of the expandable particles, and the breakage of the expandable particles when they are expanded can be suppressed. However, this presumption does not restrict or limit the present invention. The content of polyethylene glycol in the expandable particles is preferably 0.01% by weight to 0.2% by weight, more preferably 0.01% by weight to 0.15% by weight, even more preferably 0.02% by weight to 0.1% by weight, and particularly preferably 0.02% by weight to 0.08% by weight. If the content of polyethylene glycol is within this range, excellent gloss can be achieved without adversely affecting other properties of the foamed molded article.
[0028] The surface additive preferably contains an aliphatic compound that is liquid at 5°C. The aliphatic compound can typically function as a fusion promoter. Examples of the aliphatic compound include medium-chain fatty acid triglycerides. Medium-chain fatty acids refer to linear or branched fatty acids having 5 to 12 carbon atoms. By introducing the aliphatic compound into the surface additive, as in the case of the polyethylene glycol, the average number of holes per unit area on the surface of the expanded beads can be reduced in particular. The content of the aliphatic compound in the expandable beads (effectively the amount applied during production) is preferably 0.01% by weight to 0.3% by weight, more preferably 0.01% by weight to 0.25% by weight, and even more preferably 0.01% by weight to 0.1% by weight. When the content of the aliphatic compound is within such a range, excellent gloss can be achieved without adversely affecting other properties of the expanded molded product.
[0029] Preferably, polyethylene glycol and the aliphatic compound can be used in combination. By using them in combination, a synergistic effect can be obtained, and the above effect becomes more remarkable. Furthermore, the following effects can be obtained. Usually, when the medium chain fatty acid triglyceride is contained at about 0.05% by weight (substantially, applied), the gloss of the obtained foamed molded article may be insufficient. On the other hand, by using them in combination in this way, even if a high concentration of medium chain fatty acid triglyceride is used, excessive plasticization of the surface of the expandable particles can be suppressed, and therefore, breakage during expansion of the expandable particles can be suppressed. As a result, a foamed molded article having excellent gloss can be obtained. When used in combination, the blending ratio of the polyethylene glycol and the aliphatic compound (polyethylene glycol / aliphatic compound) is preferably 1.1 to 7.0, more preferably 1.2 to 6.0.
[0030] The surface additive preferably contains a metal salt of a higher fatty acid. The metal salt of a higher fatty acid can typically function as a binding inhibitor. Typical examples of the metal salt of a higher fatty acid include zinc stearate and magnesium stearate. These may be used alone or in combination. The content of the metal salt of a higher fatty acid in the expandable particles is preferably 0.0025% by weight to 0.475% by weight, more preferably 0.01% by weight to 0.3% by weight, even more preferably 0.05% by weight to 0.2% by weight, and particularly preferably 0.1% by weight to 0.2% by weight. The content of the metal salt of a higher fatty acid in the surface additive is preferably 5% by weight to 95% by weight, more preferably 20% by weight to 85% by weight, and even more preferably 35% by weight to 80% by weight. The content of the metal salt of a higher fatty acid can be converted from the amount of metal measured by, for example, inductively coupled plasma (ICP) emission spectrometry.
[0031] Other examples of surface additives include stearic acid triglyceride (typically, may function as a fusing promoter), stearic acid monostearate (typically, may function as an antistatic agent), and silicone oil (typically, may function as a lubricant).
[0032] B-4.Other The expandable particles may contain a foaming assistant together with the foaming agent. Examples of the foaming assistant include diisobutyl adipate, toluene, cyclohexane, ethylbenzene, liquid paraffin, coconut oil, and the like.
[0033] The expandable particles may further contain additives other than the above surface additives. Examples of additives include radiant heat transfer suppressing components, resins other than styrene-based resins, crosslinking agents, plasticizers, fillers, flame retardants, flame retardant assistants, lubricants, colorants, cell regulators, weather resistance agents, antioxidants, antifogging agents, and fragrances. The type, number, combination, and content of additives can be appropriately set according to the purpose.
[0034] C. Pre-expanded styrene resin particles The pre-expanded particles are obtained by pre-expanding the expandable particles described in the above item B. The pre-expanding includes expanding the expandable particles to a desired bulk expansion ratio (bulk density) using steam or the like. The bulk expansion ratio of the pre-expanded particles is preferably 3 to 100 times, more preferably 30 to 90 times, and further preferably 50 to 70 times. The bulk density is the reciprocal of the bulk expansion ratio. The bulk expansion ratio and the bulk density can be determined, for example, as follows. The expandable particles are collected as a measurement sample, W (g). The measurement sample is allowed to fall naturally into a measuring cylinder, and the volume of the measurement sample that fell into the measuring cylinder, V (cm 3 ) is measured using an apparent density measuring device conforming to JIS K 6911. From the mass and volume of the measurement sample, the bulk expansion ratio and bulk density can be calculated according to the following formula. Bulk foaming ratio (times = cm 3 / g) = volume of measurement sample (V) / mass of measurement sample (W) Bulk density (g / cm 3 ) = mass of measurement sample (W) / volume of measurement sample (V)
[0035] The pre-expanded particles can be typically expanded and molded in a mold of a predetermined shape to form an expanded molded article, as described above. The pre-expanded particles can be used as they are as a buffer material, a heat insulating material, etc. When the pre-expanded particles are used as they are, the pre-expanded particles can preferably be used as a packed body in which a large number of the pre-expanded particles are filled in a bag.
[0036] D. Method for producing expandable styrene resin particles The foamed molded article according to the embodiment of the present invention can be realized typically by using the expandable particles described in the above section B (and therefore the pre-expanded particles described in the above section C). Therefore, the embodiment of the present invention also includes a method for producing such expandable particles. The production method includes a step of polymerizing a styrene-based monomer; a step of impregnating the expandable particles with a blowing agent simultaneously with or after the polymerization to obtain expandable particles; and a step of applying a surface additive containing polyethylene glycol and / or an aliphatic compound that is liquid at 5°C to the obtained expandable particles. A representative example of a method for polymerizing a styrene-based monomer is a suspension polymerization method. The suspension polymerization method is a method in which a polymerization initiator is dissolved in a styrene-based monomer, and the monomer is heated and polymerized together with water in which a suspension agent is dispersed in a reaction tank, and then cooled to obtain expandable particles. A method in which a blowing agent is added during and / or after the completion of polymerization is called a one-stage method. The method of sieving the particles obtained by polymerization without adding a blowing agent, and then heating only the particles in the required particle size range in water with a suspended agent dispersed in a reaction tank, and adding a blowing agent to impregnate the particles therein, is called the two-stage method (post-impregnation method). Also, the method of putting small styrene resin particles (seed particles) into a reaction tank containing water with a suspended agent dispersed therein, heating it, and then continuously supplying a monomer with a polymerization initiator dissolved therein to the reaction tank to polymerize and grow the particles to the desired particle size is called the seed polymerization method. In the seed polymerization method, the blowing agent is added during and / or after the polymerization is completed. Expandable particles can be produced by any of the one-stage method, two-stage method (post-impregnation method), and seed polymerization methods. Also, all of these methods have the advantage of producing spherical expandable particles.
[0037] As the polymerization initiator in the polymerization of styrene-based monomers, any suitable radical-generating polymerization initiator can be used. Specific examples include organic peroxides such as benzoyl peroxide, t-butylperoxy-2-ethylhexanoate, t-butylperoxybenzoate, t-butylperoxy-2-ethylhexyl monocarbonate, dicumyl peroxide, t-butylperoxypivalate, t-butylperoxyisopropyl carbonate, 2,2-t-butylperoxybutane, t-butylperoxy-3,3,5-trimethylhexanoate, and di-t-butylperoxyhexahydroterephthalate; and azo compounds such as azobisdimethylvaleronitrile. These polymerization initiators can be used alone or in combination of two or more. Usually, in order to adjust the molecular weight and reduce the amount of residual monomers, a polymerization initiator having a decomposition temperature in the range of 50 to 80°C to obtain a half-life of 10 hours and a polymerization initiator having a decomposition temperature in the range of 80 to 120°C are used in combination. The polymerization initiator is preferably added as a liquid since it is necessary to uniformly absorb it into the seed particles. If the polymerization initiator is added directly to the aqueous suspension, it is difficult to uniformly absorb it into the seed particles, so it is preferable to add the polymerization initiator in a suspended or emulsified state in an aqueous medium, or to dissolve it in a small amount of a styrene-based monomer, add an inorganic suspension stabilizer and / or an anionic surfactant, and add it as an aqueous suspension.
[0038] In another embodiment, the expandable microparticles can be produced by a melt extrusion method. The melt extrusion method is a method in which styrene resin pellets are supplied to a resin supplying device, a foaming agent is injected and kneaded into the styrene resin melted in the resin supplying device, and the molten resin containing the foaming agent is extruded from a small hole in a die attached to the tip of the resin supplying device, and then cooled to obtain expandable particles. A method in which the resin is directly extruded from a small hole in a die into a cooling liquid, the extrudate is cut with a rotary blade immediately after extrusion, and the cut particles are cooled in the cooling liquid is called a hot cut method. A method in which the resin is extruded once in a strand shape from a small hole in a die into the air, introduced into a cooling water tank before the strand foams, and the strand is cooled in the cooling water tank and then cut to form cylindrical particles is called a strand cut method (cold cut method). Expandable particles can be produced by either the hot cut method or the strand cut method (cold cut method). The hot cut method has the advantage of being able to obtain almost spherical expandable particles.
[0039] In an embodiment of the present invention, as described above, a surface additive containing polyethylene glycol and / or an aliphatic compound that is liquid at 5°C is applied to the obtained expandable particles. Details of the surface additive are as described in B-3 above. Since polyethylene glycol and the above aliphatic compound are liquid, by introducing at least one of them into the surface additive, the spreading on the expandable particle surface becomes much more uniform than when only a powder surface additive is applied. As a result, the average bubble diameter of the surface layer of the pre-expanded particles and the average number of holes per unit area on the surface of the expanded particles can be controlled within the above-mentioned predetermined range. In particular, the average number of holes per unit area on the surface of the expanded particles can be reduced. Finally, an expanded molded product with excellent gloss can be obtained.
[0040] In the above-described manufacturing method, the desired properties can be achieved without subjecting the obtained expandable granules to hot air treatment. Therefore, the manufacturing method of the expandable granules according to the embodiment of the present invention is excellent in manufacturing efficiency.
[0041] E. Method for producing styrene-based resin foam molded products The embodiment of the present invention also includes a method for producing a foamed molded article. The method uses expandable particles obtained by the method described in the above section D. The foamed molded article can be produced, typically, by charging pre-expanded particles into a mold having a predetermined shape according to the purpose and performing in-mold foaming. The pre-expanded particles can be obtained by pre-expanding the expandable particles obtained by the method described in the above section D. The in-mold foaming includes (i) filling the pre-expanded particles into a closed mold having a large number of small holes, (ii) heating and expanding the pre-expanded particles with a heat medium (e.g., pressurized steam, etc.) to obtain expanded particles, and (iii) filling the voids between the expanded particles by the heat expansion and fusing the expanded particles to each other to integrate them. The density of the foamed molded article can be appropriately set according to the purpose. The density of the foamed molded article can be adjusted, for example, by adjusting the bulk expansion ratio of the pre-expanded particles to be filled in the mold in advance, or by adjusting the amount of pre-expanded particles filled in the mold.
[0042] The heat-foaming temperature (substantially the temperature of the heat transfer medium) is preferably 90°C to 150°C, more preferably 110°C to 130°C. The heat-foaming time is preferably 5 seconds to 50 seconds, more preferably 10 seconds to 50 seconds. The molding vapor pressure of the heat-foaming (gauge pressure of the heat transfer medium blowing in) is preferably 0.06 MPa to 0.08 MPa. If the heat-foaming is performed under such conditions, the expanded particles can be well fused to each other.
[0043] If necessary, the pre-expanded particles may be aged before forming into a foamed molded article. The aging temperature of the pre-expanded particles is preferably 20°C to 60°C. If the aging temperature is too low, an excessively long aging time may be required. If the aging temperature is too high, the blowing agent in the pre-expanded particles may dissipate, resulting in a decrease in moldability.
[0044] The bulk expansion ratio of the expanded beads in the expanded molded product is preferably 3 to 100 times, more preferably 30 to 90 times, and further preferably 50 to 70 times.
[0045] As described above, the foamed molded article can be produced. The foamed molded article thus obtained has excellent gloss.
Examples
[0046] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. The measurement methods and evaluation methods for each property are as follows.
[0047] (1) Residual monomer content of expandable particles The residual monomer content of the expandable particles was measured by gas chromatography. Specifically, it is as follows. 1 g of the expandable particles obtained in the examples and comparative examples was precisely weighed, and 1 mL of a dimethylformamide solution containing 0.1% by volume of cyclopentanol was added as an internal standard solution to the precisely weighed sample. Then, dimethylformamide was further added to prepare a 25 mL measurement solution. Next, 1.8 μL of this measurement solution was supplied to a gas chromatograph (manufactured by Shimadzu Corporation, trade name "GC-2014") for measurement. Based on the calibration curve of the styrene monomer measured in advance, the amount of the styrene monomer in the measurement solution was calculated, and the residual monomer content (ppm) with respect to the total weight of the expandable particles was calculated. The measurement conditions are as follows. <GC measurement conditions> Detector: FID Column: manufactured by GL Sciences Inc. (φ3 mm × 2 m) Liquid phase: PEG-20MPT25% Carrier: Chromosorb WAW-DWCS Mesh: 60 / 80 Column temperature: 95 °C DET temperature: 220 °C Detector temperature: 220 °C Carrier gas: nitrogen Nitrogen flow rate: 40 mL / min
[0048] (2) Surface additive content of expandable particles 20 g of the expandable particles obtained in the examples and comparative examples were placed in a 50 mL Erlenmeyer flask and weighed accurately. About 30 mL of reagent grade methanol was poured into this Erlenmeyer flask. After sealing, it was shaken well by hand, the contents of the Erlenmeyer flask were stirred with a stirrer bar for 2 hours, and the supernatant was filtered through a 200 mesh wire mesh. The beaker containing the filtrate was naturally dried in a draft chamber to evaporate the methanol, and the beaker was further dried in a thermostatic oven at 120°C for 2 hours. The beaker after drying was left to cool in a desiccator, filtered through a wire mesh, the extract was collected in a beaker, and then dried together with the beaker. The amount of surface additive extracted by methanol was calculated from the weight of the beaker before and after drying, and was taken as the surface additive content. The calculation formula is as follows. Surface additive content (mass%) = m1 / m0 x 100 m0: initial mass of the sample m1: mass of surface additive (M1-M0) M0: initial mass of the beaker M1: Total mass of surface additive and beaker
[0049] (3) Zinc stearate or magnesium stearate content of expandable particles About 1.0 g of the expandable particles obtained in the examples and comparative examples was precisely weighed and placed in a 50 mL Erlenmeyer flask. 10 mL of 5N hydrochloric acid was added to the Erlenmeyer flask, the lid was securely closed, and the mixture was stirred for 10 minutes. Then, 20 mL of ultrapure water was added and the mixture was stirred for another 20 minutes. The insoluble matter in the Erlenmeyer flask was filtered with No. 7 filter paper manufactured by ADVANTEC. The filtrate was used as a test liquid and the zinc element concentration and magnesium element concentration were measured under the following conditions. The zinc concentration and magnesium concentration of the test liquid were obtained from the calibration curve, and the zinc amount and magnesium amount in the sample were calculated. Furthermore, the zinc amount was converted to zinc stearate, and the magnesium amount was converted to magnesium stearate, and the converted zinc stearate amount and magnesium stearate amount in the sample were calculated from the following formula. Zinc amount (mass%) = zinc concentration (μg / mL) × 30 (mL) ÷ sample mass (g) ÷ 10,000 Converted amount of zinc stearate (% by mass) = amount of zinc (% by mass) × (632.33 / 65.38) Magnesium content (mass %) = Magnesium concentration (μg / mL) × 30 (mL) ÷ Sample mass (g) ÷ 10,000 Magnesium stearate equivalent content (mass %) = Magnesium content (mass %) × (591.26 / 24.31) <ICP measurement conditions> Measuring device: "ICP-9000" multi-type ICP emission spectroscopic analyzer manufactured by Shimadzu Corporation Measured elements: Zinc (202.548 nm), Magnesium (285.213 nm) Observation direction: Axial direction RF output: 1.20 kw Carrier gas flow rate: 0.7 mL / min Plasma gas flow rate: 10.0 mL / min Auxiliary gas flow rate: 0.6 mL / min Exposure time: 30 seconds Standard solution for calibration curve: "XSTC-13" general-purpose mixed standard solution of 31 elements (base 5% HNO3) approximately 10 mg / L manufactured by SPEX Industries, Inc., USA
[0050] (4) Polyethylene glycol content of the expandable particles 1.0 g of the expandable particles obtained in the examples and comparative examples was precisely weighed into a 50 mL Erlenmeyer flask. 20 mL of methanol for HPLC was added dropwise with a whole pipette. Stirred with a stir bar for 60 minutes, and the supernatant was filtered through a non-aqueous 0.20 μm chromatographic disk. The measurement conditions were as shown below. Using the PEG peak area value obtained from the chromatogram, the PEG concentration in the sample solution was determined from the calibration curve. The PEG amount on the sample surface was calculated from the obtained results. Note that the standard PEG for the calibration curve used was PEG-300 (manufactured by Sanyo Chemical Industries, Ltd.). (HPLC measurement conditions) Device: "Ultimate3000" high-performance liquid chromatograph manufactured by Thermo SCIENTIFIC Column: Acclaim RSCL 120 C18 2.2 μm (2.1 mm I.D. × 50 mm L) manufactured by Thermo SCIENTIFIC Column temperature: 40 °C Mobile phase: Distilled water / Methanol = 15 / 85 Flow rate: 0.5mL / min Pump temperature: Room temperature Injection volume: 2μL Detector: Thermo SCIENTIFIC "CAD Corona VeoRS" charged particle detector
[0051] (5) Average cell diameter of the surface layer of pre-expanded particles The average bubble diameter was measured according to the test method of ASTM D2842-69. Specifically, 10 randomly selected pre-expanded particles (bulk expansion ratio 60 times) obtained in the examples and comparative examples were divided into two equal parts using a razor blade along a plane passing near the center of the pre-expanded particles, and one of the cut surfaces was photographed at 60 times magnification using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, "SU1510"), with the outside of a circle equivalent to 50% of the radius from the center of the pre-expanded particles. Next, the photographed image was printed on A4 paper, and a straight line 60 mm long was drawn at an arbitrary location on the surface layer (a region from the surface of the pre-expanded particles to 200 μm toward the center), and the average chord length (t1) of the bubbles was calculated from the number of bubbles present on this straight line using the following formula. Average chord length t1 (μm) = 60 / (number of bubbles × magnification of photo) In addition, when drawing the straight line, the straight line was made to penetrate the air bubbles as much as possible without making point contact with them. If some of the air bubbles made point contact with the straight line, these air bubbles were also included in the number of air bubbles, and if both ends of the straight line were located inside the air bubbles without penetrating them, the air bubbles where both ends of the straight line were located were also included in the number of air bubbles. Then, the air bubble diameter was calculated using the following formula based on the calculated average chord length t1. Average bubble diameter D1 (μm) = t1 / 0.616 The bubble diameter was calculated in any three locations of the captured image in the same manner as described above, and the arithmetic mean value of the bubble diameters in a total of five images (total of 15 locations) was taken as the average bubble diameter of the pre-expanded styrene-based resin particles.
[0052] (6) Average cell diameter in the surface layer of the foamed molded product The average bubble diameter was measured in accordance with the test method of ASTM D2842-69. Specifically, the foam molded articles obtained in the examples and comparative examples were cut using a razor blade so that the cross section near the surface of the foam molded article could be observed. The cut surface was photographed at 50 times magnification using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, "SU1510"). Next, the photographed image was printed on A4 paper, and a straight line with a length of 60 mm was drawn at an arbitrary location on the surface layer portion (a region from the surface of the foam molded article to 500 μm inward in a direction perpendicular to the surface (i.e., in the thickness direction)), and the average chord length (t2) of the bubbles was calculated from the number of bubbles present on this straight line using the following formula. Average chord length t2 (μm) = 60 / (number of bubbles × magnification of photo) In drawing the straight line, the straight line was made to penetrate the cells as much as possible without making point contact with them, and to be within each particle without spanning between foamed particles. If some of the cells made point contact with the line, these cells were also included in the cell count, and if both ends of the line were located within the cells without penetrating them, the cells where both ends of the line were located were also included in the cell count. The cell diameter was calculated from the average chord length t2 calculated in this way using the following formula. Average bubble diameter D2 (μm)=t2 / 0.616 The bubble diameter was calculated in the same manner as described above at any three points in the captured image, and the arithmetic mean value of the bubble diameters in a total of five images (15 points in total) was taken as the average bubble diameter in the surface layer of the foamed molded article.
[0053] (7) Average number of pores per unit area on the surface of the foamed beads The surface of the foamed molded article obtained in the examples and comparative examples was cut into a piece of about 1 cm square and about 1 mm thick using a razor blade. Next, the foamed particles constituting the surface of the foamed molded article were photographed at 30 times magnification using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, "SU1510"). From the photographed image, it was possible to determine the surface of the foamed particles constituting the surface of the foamed molded article within 1 mm. 2The number of holes of 20 μm or more that had occurred due to broken bubbles was counted per unit area, and measurements were taken at 10 random locations to calculate the average value. When measuring, the measurement range was set to end on the surface of the foamed particles that constitute the surface of the foamed molded product, so as not to measure between the particles.
[0054] (8) Surface roughness Rzjis94 The foamed molded articles obtained in the examples and comparative examples were allowed to stand for 24 hours in a thermostatic chamber set at 24°C. Next, the surface roughness (10-point average roughness Rzjis94) of the foamed particles constituting the surface of the flat-shaped foamed molded article was measured using a surface roughness shape measuring instrument (manufactured by Tokyo Seimitsu Co., Ltd., product name "HANDYSURF E-35A"). During the measurement, the measurement range was set to end on the surface of the foamed particles constituting the foamed molded article surface so as not to measure between the particles. The measurement was performed at any 20 points on the foamed molded article surface, and the average value was taken as the surface roughness (10-point average roughness Rzjis94). The measurement conditions were as follows. <Surface roughness measurement conditions> Pickup model: E-DT-SM10A Cutoff value λc: 0.25 mm Evaluation length L: 1.4 mm Measurement unit: μm Calculation standard: JIS'94
[0055] (9) Gloss The foamed molded articles obtained in the examples and comparative examples were allowed to stand for 24 hours in a thermostatic chamber set at 24°C. Next, using a gloss meter (Horiba, Ltd., "Gloss Checker IG-331"), the gloss of any 20 points on the surface of the foamed molded article was measured at 60° (incident angle 60°, receiving angle 60°), and the average value was taken as the gloss. From the obtained gloss, the gloss of the foamed molded article was evaluated according to the following criteria. ◎ (Excellent): 27 or above 〇(Good) :24~26 △(Acceptable): 21~23 × (defective): 20 or less
[0056] [Example 1] <Production of Expandable Styrene-Based Resin Particles> In a 100-liter polymerization vessel equipped with a stirrer, 40,000 parts by mass of water, 100 parts by mass of tricalcium phosphate as a suspension stabilizer, and 3.2 parts by mass of sodium dodecylbenzenesulfonate as an anionic surfactant were supplied, and 40,000 parts by mass of styrene and 102 parts by mass of benzoyl peroxide and 24 parts by mass of t-butylperoxy-2-ethylhexyl monocarbonate as a polymerization initiator were added while stirring, and the temperature was raised to 90°C to polymerize. The reaction system was kept at this temperature for 6 hours, and then heated to 125°C and cooled after 2 hours to obtain styrene-based resin particles. The obtained styrene-based resin particles were sieved to obtain styrene-based resin particles having a particle diameter of 0.5 to 0.71 mm as seed particles. The rotation speed of the stirrer was adjusted so that the above particle diameter was obtained. Next, 2150 parts by mass of seed particles, 30 parts by mass of magnesium pyrophosphate, and 1.0 part by mass of sodium dodecylbenzenesulfonate were supplied to a 25-liter polymerization vessel equipped with a stirrer, and heated to 72°C while stirring to prepare a dispersion. Next, a solution obtained by dissolving 31 parts by mass of benzoyl peroxide, 8 parts by mass of t-butylperoxy-2-ethylhexyl monocarbonate, and 0.7 parts by mass of didodecyl 3,3'-thiodipropionate as a cell regulator in a monomer mixture of 786 parts by mass of styrene and 137 parts by mass of butyl acrylate was supplied to the dispersion while stirring. After all the solution was supplied, the reaction system was maintained at 72°C for 60 minutes. Next, the reaction system was heated to 87°C over 1 hour while constantly feeding 2346 parts by mass of styrene, and further, while maintaining at 87°C for 1 hour and 30 minutes, a monomer mixture in which 2.7 parts by mass of divinylbenzene was dissolved in 3744 parts by mass of styrene was constantly fed, and maintained for another 30 minutes. Next, the reaction system was heated to 125°C and maintained for 30 minutes to react the unreacted monomers. Next, the reaction system was cooled to 100°C, and 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 45 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel and maintained for 2 hours, and then the inside of the polymerization vessel was cooled to 25°C to obtain expandable particles. The resulting expandable particles were coated with a surface additive, which was prepared so as to contain 0.15 parts by mass of zinc stearate, 0.07 parts by mass of stearate triglyceride, 0.05 parts by mass of stearate monostearate, 0.08 parts by mass of polyethylene glycol, and 0.01 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of the expandable particles.
[0057] <Production of pre-expanded styrene-based resin particles> The expandable particles coated with the surface additive were left in a thermostatic chamber at 13° C. for 5 days. The expandable particles were then heated to a bulk density of 0.0166 g / cm 3 The mixture was pre-expanded to a volume expansion ratio of 60 to obtain pre-expanded particles.
[0058] <Production of styrene resin foam molded products> The pre-expanded particles obtained above were aged at 20°C for 24 hours. Next, the pre-expanded particles were left in a room temperature atmosphere for 24 hours, and then in-mold foam molding was performed. For in-mold foam molding, an ACE-3SP molding machine manufactured by Sekisui Koki Co., Ltd. was used to foam mold 400mm x 300mm x 30mm. The heating time was one-sided heating time 8 seconds, reverse one-sided heating time 2 seconds, and both-sided heating time 5 seconds, and the molding pressure (steam injection gauge pressure) was 0.06MPa. In this way, a foam molded body was obtained. The obtained foam molded body was subjected to the evaluation of (9) above. The results are shown in Table 1. In Table 1, "aliphatic compound" refers to an aliphatic compound that is liquid at 5°C (medium-chain fatty acid triglyceride in this example).
[0059] [Example 2] Expandable particles were obtained in the same manner as in Example 1, except that 0.98 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator, and 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 49 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.18 parts by mass of zinc stearate, 0.03 parts by mass of triglyceride stearate, 0.03 parts by mass of polyethylene glycol, and 0.02 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that the expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0060] [Example 3] Expandable particles were obtained in the same manner as in Example 1, except that 0.77 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator. A surface additive containing 0.15 parts by mass of zinc stearate, 0.05 parts by mass of monostearate stearate, 0.08 parts by mass of polyethylene glycol, and 0.03 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that these expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0061] [Example 4] Expandable particles were obtained in the same manner as in Example 1, except that 1.40 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator. A surface additive containing 0.18 parts by mass of zinc stearate, 0.03 parts by mass of triglyceride stearate, 0.03 parts by mass of polyethylene glycol, and 0.02 parts by mass of medium-chain triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that these expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0062] [Example 5] Expandable particles were obtained in the same manner as in Example 1, except that 1.54 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator, and 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 52 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.18 parts by mass of zinc stearate, 0.03 parts by mass of triglyceride stearate, 0.03 parts by mass of polyethylene glycol, and 0.02 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that the expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0063] [Example 6] Expandable particles were obtained in the same manner as in Example 1, except that 1.44 parts by mass of didodecyl 3,3'-thiodipropionate was used as the cell regulator. A surface additive containing 0.18 parts by mass of zinc stearate, 0.03 parts by mass of triglyceride stearate, 0.03 parts by mass of polyethylene glycol, and 0.02 parts by mass of medium-chain triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that the expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0064] [Example 7] Expandable particles were obtained in the same manner as in Example 1, except that 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 2 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. Pre-expanded particles and foamed molded articles were obtained in the same manner as in Example 1. The obtained foamed molded articles were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0065] [Example 8] Expandable particles were obtained in the same manner as in Example 1, except that 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 7 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. Pre-expanded particles and foamed molded articles were obtained in the same manner as in Example 1. The obtained foamed molded articles were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0066] [Example 9] Expandable particles were obtained in the same manner as in Example 1, except that 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 30 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. Pre-expanded particles and foamed molded articles were obtained in the same manner as in Example 1. The obtained foamed molded articles were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0067] [Example 10] Expandable particles were obtained in the same manner as in Example 1, except that 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 90 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. Pre-expanded particles and foamed molded articles were obtained in the same manner as in Example 1. The obtained foamed molded articles were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0068] [Example 11] Expandable particles were obtained in the same manner as in Example 1, except that 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 70 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.15 parts by mass of zinc stearate, 0.04 parts by mass of stearic acid triglyceride, 0.05 parts by mass of stearic acid monostearate, 0.08 parts by mass of polyethylene glycol, and 0.04 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that these expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0069] [Example 12] Expandable particles were obtained in the same manner as in Example 1, except that 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 70 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.025 parts by mass of zinc stearate, 0.02 parts by mass of polyethylene glycol, and 0.01 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that these expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0070] [Example 13] Except for using magnesium stearate instead of zinc stearate as the surface additive, pre-expanded particles and foamed molded articles were obtained in the same manner as in Example 1. The obtained foamed molded articles were subjected to the same evaluations as in Example 1. The results are shown in Table 1.
[0071] [Example 14] Expandable particles were obtained in the same manner as in Example 1. A surface additive containing 0.15 parts by mass of zinc stearate, 0.07 parts by mass of triglyceride stearate, 0.05 parts by mass of monostearate stearate, and 0.08 parts by mass of polyethylene glycol per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded products were obtained in the same manner as in Example 1, except that these expandable particles were used. The obtained foamed molded products were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0072] [Comparative Example 1] Expandable particles were obtained in the same manner as in Example 1, except that 0.98 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator, and 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 1.5 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.015 parts by mass of zinc stearate, 0.5 parts by mass of triglyceride stearate, and 0.05 parts by mass of monostearate stearate per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that the expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0073] [Comparative Example 2] Expandable particles were obtained in the same manner as in Example 1, except that 1.40 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator, and 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 135 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.015 parts by mass of zinc stearate, 0.07 parts by mass of triglyceride stearate, 0.23 parts by mass of polyethylene glycol, and 0.4 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that the expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0074] [Comparative Example 3] Expandable particles were obtained in the same manner as in Example 1, except that 1.40 parts by mass of didodecyl 3,3'-thiodipropionate was used as a cell regulator, and 92 parts by mass of cyclohexane, 82 parts by mass of diisobutyl adipate, 45 parts by mass of styrene, and 640 parts by mass of mixed butane were pressed into the polymerization vessel during the foaming agent impregnation. A surface additive containing 0.015 parts by mass of zinc stearate, 0.07 parts by mass of triglyceride stearate, 0.23 parts by mass of polyethylene glycol, and 0.4 parts by mass of medium-chain fatty acid triglyceride per 100 parts by mass of expandable particles was applied to the expandable particles. Pre-expanded particles and foamed molded bodies were obtained in the same manner as in Example 1, except that the expandable particles were used. The obtained foamed molded bodies were subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0075] [Table 1]
[0076] As is apparent from Table 1, according to the embodiments of the present invention, by controlling within a predetermined range the average bubble diameter of the surface layer of the pre-expanded styrene-based resin particles forming the styrene-based resin foam and the average number of holes per unit area on the surface of the expanded styrene-based resin particles constituting the foam, a styrene-based resin foam with excellent gloss can be realized. [Industrial Applicability]
[0077] The styrene-based resin foam molded article according to the embodiment of the present invention is suitable for use as an insulating material for houses and automobiles, etc., a heat-retaining material for building materials, etc., a transport packaging material for fish boxes and food containers, a cushioning material, etc. More specifically, the styrene-based resin foam molded article is suitable for use as a wall insulating material, a floor insulating material, a roof insulating material, an automobile insulating material, a hot water tank insulating material, a piping insulating material, a solar system insulating material, a water heater insulating material, a container for food and industrial products, etc., a packaging material for fish and agricultural products, etc., a banking material, a tatami mat core material, etc.
Claims
1. A styrene-based resin foamed molded article comprising a plurality of fused styrene-based resin particles obtained by expanding pre-expanded styrene-based resin particles, the styrene-based resin particles being foamed together, The average number of pores on the surface of the expanded styrene resin particles present on the surface of the styrene resin expanded molded product is 20 pores / mm 2 is less than the surface roughness Rzjis94 of the expanded styrene resin particles present on the surface of the styrene resin expansion molded product is 1 μm to 25 μm; the residual monomer content of the expandable styrene-based resin particles forming the pre-expanded styrene-based resin particles is 200 ppm to 10,000 ppm, and the content of the surface additive in the expandable styrene-based resin particles is 0.05% by weight to 0.5% by weight; the surface additive contains polyethylene glycol, and the content of the polyethylene glycol in the expandable styrene-based resin particles is 0.01% by weight to 0.1% by weight; the surface additive contains an aliphatic compound that is liquid at 5°C, and the content of the aliphatic compound in the expandable styrene-based resin particles is 0.01% by weight to 0.3% by weight; the blending ratio of the polyethylene glycol to the aliphatic compound (polyethylene glycol / aliphatic compound) is 1.1 to 7.0; Styrene resin foam molding.
2. The styrene-based resin foam molded article according to claim 1, wherein the average bubble diameter of the surface layer of the styrene-based resin foam molded article is 25 μm to 250 μm.
3. 3. The styrene-based resin foam molded article according to claim 1, wherein the aliphatic compound which is liquid at 5° C. is a medium-chain fatty acid triglyceride.
4. The surface additive comprises a metal salt of a higher fatty acid, and the content of the metal salt of a higher fatty acid in the expandable styrene-based resin particles is 0.0025% by weight to 0.475% by weight. The styrene-based resin foamed molded article according to any one of claims 1 to 3.
5. 5. The styrene-based resin foam molded article according to claim 4, wherein the metal salt of a higher fatty acid is at least one selected from the group consisting of zinc stearate and magnesium stearate.
6. A method for producing expandable styrene-based resin particles, comprising the steps of: polymerizing a styrene-based monomer; A step of impregnating the polymer with a blowing agent simultaneously with or after the polymerization to obtain expandable particles; applying to the expandable granules a surface additive comprising polyethylene glycol and an aliphatic compound that is liquid at 5° C.; Including, The expandable granules have a residual monomer content of 200 ppm to 10,000 ppm; The content of the surface additive in the expandable particles is 0.05% by weight to 0.5% by weight, a blending ratio of the polyethylene glycol to the aliphatic compound (polyethylene glycol / aliphatic compound) of 1.1 to 7.
0.
7. A method for producing a styrene-based resin foamed molded article according to any one of claims 1 to 5, which uses expandable styrene-based resin particles obtained by the method for producing the styrene-based resin foamed molded article according to claim 6.
Citation Information
Patent Citations
JP1971001338Y1
JP1974025620A
JP1974082302A
JP1975014653A
Expandable styrenic resin particle and its production
JP1994122781A